Incidence of Infectious Complications Following Cochlear Implantation in Children and Adults - Lander, Daniel P. (JAMA, 2020)
This cohort study uses data from state health care databases to determine the incidence and timing of infectious complications following cochlear implant surgery among patients in 5 US states between 2006 and 2016.